A narrative action on the battle against hunger using mushroom, peanut, and soybean-based wastes - Mohd Zaini, Nurul Aqilah; Azizan, Nur Asyiqin Zahia; Abd Rahim, Muhamad Hafiz; Jamaludin, Adi Ainurzaman; Raposo, António; Raseetha, Siva; Zandonadi, Renata Puppin; BinMowyna, Mona N.; Raheem, Dele; Lho, Linda Heejung; Han, Heesup; Wan-Mohtar, Wan Abd Al Qadr Imad (Frontiers Media, 2023)
Numerous generations have been affected by hunger, which still affects hundreds of millions of people worldwide. The hunger crisis is worsening although many efforts have been made to minimize it. Besides that, food waste is one of the critical problems faced by most countries worldwide. It has disrupted the food chain system due to inefficient waste management, while negatively impacting the environment. The majority of the waste is from the food production process, resulting in a net zero production for food manufacturers while also harnessing its potential. Most food production wastes are high in nutritional and functional values, yet most of them end up as low-cost animal feed and plant fertilizers. This review identified key emerging wastes from the production line of mushroom, peanut, and soybean (MPS). These wastes (MPS) provide a new source for food conversion due to their high nutritional content, which contributes to a circular economy in the post-pandemic era and ensures food security. In order to achieve carbon neutrality and effective waste management for the production of alternative foods, biotechnological processes such as digestive, fermentative, and enzymatic conversions are essential. The article provides a narrative action on the critical potential application and challenges of MPS as future foods in the battle against hunger.